ZEP QUIZ Upaya Memperkuat Praktik Evaluasi Pembelajaran Berbasis Digital di MTSN 2 Kota Tangerang - Hilda Mardiyana; Neli Permatasari; Yudha Ningsih; Julius Martunas Sihite; Ani Hoerunisa (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
Digital-based learning evaluation is an important effort to improve the effectiveness and efficiency of the assessment process. However, learning evaluation practices at MTsN 2 Kota Tangerang are still dominated by conventional methods and the limited use of simple digital applications. This community service activity aims to strengthen digital-based learning evaluation practices through training on the use of the Zep Quiz application for teachers. The activity employed a participatory and applicative approach, including observation, focus group discussions, training and mentoring, and program evaluation. The training was conducted in a hybrid format and focused on introducing, developing, and analyzing learning evaluations using Zep Quiz. The results indicate that teachers improved their understanding and skills in designing and operating digital-based learning evaluations independently.Teachers also demonstrated high enthusiasm and active participation throughout the activity. Although technical challenges such as varying levels of digital literacy and limited internet access were encountered, these issues were addressed through direct mentoring. Therefore, the Zep Quiz training was effective in strengthening digital-based learning evaluation practices at MTsN 2 Kota Tangerang.